(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper, we study the following Navier problem Here, h ∈ L^p' (Q, v^1−p′_1), K, L and b are Carathéodory functions and ϕ_1,ϕ_2, v_1, v_2, v_3 and v_4 are A_p-weights functions. By using the theory of monotone operators (Browder–Minty Theorem), we demonstrate the existence and uniqueness of weak solution to the above problem.